FINANCIAL PERFORMANCE AND CORPORATE VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATION OF HIGH AND LOW PROFILE COMPANIES - I Gusti Ayu Ratih Permata Dewi; Cok Istri Ratna Sari Dewi; Ni Kd. Sioaji Yamawati (Bajang Institute, 2023)
This study aims to analyze how much influence Enterprise Risk Management, Intellectual Capital, and Sustainability Report have on Company Financial Performance and Their Impact on Company Value with Good Corporate Governance as moderator in High Profile and Low Profile Companies listed on the Indonesia Stock Exchange. The population of this study is 80 High Profile and Low Profile companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Determination of the sample was carried out using purposive sampling and obtained 20 companies as samples in this study for 3 years so that a total sample of 60 companies. The data analysis technique used is Stata software. The results of this study indicate that the company's financial performance has an effect on firm value, meanwhile, enterprise risk management, intellectual capital and sustainability reports have no effect on firm value. Enterprise risk management, intellectual capital, and sustainability reports have no effect on the company's financial performance. Good corporate governance is able to moderate the effect of enterprise risk management on firm value